The Effect of a Counseling Program on Modifying the Negative Thoughts of Late Marriage Age - Siham Abu Eita; Ziad M. AL- Khazaleh (Sultan Qaboos University, 2012)
The aim of the study was to explore the effect of group counseling program based on cognitive approach in modifying the negative thoughts of late marriage -age in Jordan. The sample consisted of 20 delayed marriage - age males from Jaresh Governance. The sample members' ages exceeded 30 years old. The participants were divided into two groups: The experimental group (N=10) whose members received a group counseling based on cognitive and rational emotive therapy; consisting of 13 sessions and the control group (N=10) whose members did not receive any counseling. Negative thoughts scale was developed and applied before and after the study. In order to test the hypotheses of the study, means and standard deviations, independent samples t-test, paired samples t-test and analysis of covariance (ANCOVA) were utilized. The statistical analysis indicated that there was significant difference at (p < 0.05) in the negative thoughts between experiment and control group in post measures and there was significant differences between the post measure and the fellow up measure for the experimental group. The study ended by some recommendations such as conducting more studies to examine the ability of cognitive approach that used in current study to resolve various individual problems especially those related to cognitive knowledge or thinking.